COMPUTER DISCOVERED MATHEMATICS AND APPLICATIONS IN EDUCATION - Grozdev, Sava; Dekov, Deko (Matematichki Bilten, 2016)
The computer program “Discoverer” is the first, able easily to discover new theorems in mathematics, and possibly new knowledge in science. In the present paper the authors discuss the use of “Discoverer” in teaching and learning of geometry filling a gap in the existing educational tools. “Discoverer” provides the possibility for students easily to discover new theorems in Euclidean geometry. By using the principles of “Discoverer”, a number of similar programs could be created for high school teaching in: physics, chemistry, biology, and so on. Such programs could be considered as tools for interest activation. We call the use of “Discoverer” for educational purposes to be “learning through discovery”, which may be considered as a new important direction within “learning through inquiry”.